THE IMPACT OF FINANCIAL RATIO TOWARD STOCK PRICE: EVIDENCE FROM BANKING COMPANIES - Marvin Wijaya; Andi Ina Yustina (President University Press, 2017)
Once company stock listed in IDX it means the stocks will be control by the market. We would like to analyzed the factors that impact stock market in listed companies in ISX. The samples will be coming from Banks Companies. There are many factor that impact stock market, but the researcher only analyzed three of those. The first is dividend policy using dividend payout ratio. The second is profitability ratio using return on assets ratio and return on equity ratio. the last but not lease is solvency ratio using debt to equity ratio. The researcher used multiple regression analysis to create the research equotion. After that, in order to test the hypothesis the researcher using coefficient (R2) testand t test. Through all the test, this research present the dividend policy using dividend payout ratio and profitability ratio using return on asset ratio has significant correlation with stock price. Then, solvency ratio using debt to equity ratio and profitability using return on equity has in significant correlation with stock price.